Penggunaan Soal Cerita Terhadap Pemahaman Siswa Terkait Materi Satuan Panjang Dengan Menggunakan Metode RME - Wafa Ummul Juhwa; Luthpiyah Juliandara (Journal on Education, 2023)
The jni study aims to find out whether grade V students at SDN KARANGPAWITAN 3 understand the length unit using story questions, as well as what factors make students less aware of the story even though it has been explained. The method used in this study used a qualitative descriptive method by collecting data carried out with tests and conducting interviews with grade 5 homeroom teachers. From the results of research that has been carried out, the students have not fully understood the meaning of the story questions, but there are some students who already understand how to solve the story questions but on average the study